الترجيح بالقواعد للإمام الطبري - قمولة, شادية; شيحي, صالحة (University of eloued جامعة الوادي, 2021)
"يدور هذا البحث حول موضوع الترجيح بالقواعد عند الإمام الطبري من خلال نماذج من سورة البقرة ،وكان الهدف من هذا البحث معرفة مسالك الإمام الطبري في الترجيح بالقواعد التفسيرية التي قعدها في تفسير جامع البيان وقد قسم هذا البحث إلى مدخل فيه ترجمنا للطبري بإيجاز وثلاث مباحث: مبحثين نظريين فيهما التعريف بمصطلحات الدراسة ومفاتيح البحث كما تعرفنا على منهجه في الترجيح بالقواعد التي قعدها في تفسيره جامع البيان, ومبحث تطبيقي تناولنا من خلاله استعمال الطبري القواعد التفسيرية في الترجيح . وتبين من خلال الأمثلة المنتخبة من سورة البقرة تنوع المسالك التي وظف فيها الطبري قواعد الترجيح , فرجح باستعمال القواعد المتعلقة بالقراءات والقواعد المتعلقة باللغة والقواعد المتعلقة بالآثار وأسباب النزول وعيرها ,وكان لهذه المسالك المتنوعة أثر كبير في من جاء بعد الإمام الطبري من المفسرين ""This research revolves around the issue of weighting according to the rules of Imam al-Tabari through models from Surat al-Baqarah, and the aim of this research was to know the ways of Imam al-Tabari in weighing the explanatory rules that he used in the interpretation of Jami’ al-Bayan.This research was divided into an introduction in which we translated al-Tabari briefly and three chapters: two theoretical chapters in which the definition of the study terms and the keys of the research, as we learned about his method of weighting with the rules that he set in his interpretation of Jami’ al-Bayan, and an applied study in which we dealt with al-Tabari’s use of explanatory rules in weighting. Through the selected examples from Surat Al-Baqarah, it became clear the diversity of paths in which al-Tabari employed the rules of weighting, so he preferred the use of rules related to readings, rules related to language, rules related to antiquities, and the reasons for revelation and their disgrace."
علوم قران
Keywords: الترجيح/الامام الطبري; Weighting by rules - Imam al-Tabari - the elected actress